The "Coastal Cajamarca" Style Did Not Comefrom The Coast. (2nd January 2019) - Tsai, Howard
Abstract : The Coastal Cajamarca style of pottery was first reported on the north coast of Peru and subsequently interpreted as an emulation of highland Cajamarca ceramics by coastal potters. Alternatively, some researchers proposed an origin of the style in the chaupiyunga, or the intermediary area between the coast and the highlands on the western slope of the Andes. This article presents excavation data from the site of Las Varas, an 11th-century village located in the Middle Jequetepeque Valley, to support the chaupiyunga-origin hypothesis. The quantity of Coastal Cajamarca sherds recovered from Las Varas (3, 223) accounted for more than a third of the total number of diagnostic pottery, making it the dominant style of the site; this sample revealed a variety of motifs and designs not documented in coastal sites. Other vessels in Las Varas' ceramic assemblage – domestic ware used for cooking and storage – resembled highland Cajamarca pottery in form and surface decoration.